Tren Keuangan: Analisis Rasio Kinerja PT. Telekomunikasi Indonesia Tbk untuk Menilai Kesehatan Keuangan Perusahaan - St. Salmah Sharon; R.A. Widyanti Diah Lestari; Anny widiasmara; Syamsul Bahri (Prodi Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas PGRI Madiun, 2024)
This research aims to analyze the financial trends of PT. Telekomunikasi Indonesia Tbk (Telkom) from 2020 to 2022 uses performance ratio analysis as a tool to evaluate the company's financial health. Through the use of financial ratio analysis methods, this study explores various aspects of Telkom's financial performance, including profitability, liquidity, solvency and operational efficiency, as well as tracking changes that occurred during that period. The analysis results show that Telkom shows relative stability in its profitability, even though it faces liquidity challenges in 2021 due to the impact of the COVID-19 pandemic. However, the company's solvency ratio shows a consistent increase, indicating Telkom's ability to meet long-term financial obligations. In addition, this study also identifies several areas where Telkom can improve its operational efficiency, such as in asset management and inventory management. These findings provide valuable insights for stakeholders to understand Telkom's financial condition and to take the necessary strategic steps to strengthen the company's financial health in the future